Diaphragm for alkaline water electrolysis, and method for producing the same
The alkaline water electrolysis diaphragm with a polymer-based coating layer addresses the issue of inorganic particle removal, improving durability and performance while maintaining film resistance.
Patent Information
- Application Number
- JP2023172915
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-16
AI Technical Summary
Existing alkaline water electrolysis diaphragms face challenges in suppressing the removal of inorganic particles, which affects their performance and durability.
The development of an alkaline water electrolysis diaphragm with a coating layer containing a polymer having an acid group, applied on one or both sides of a porous support and porous membrane, which includes inorganic particles and an organic resin. This coating layer helps to bond the inorganic particles and retain them within the diaphragm.
The proposed solution effectively prevents the removal of inorganic particles, enhancing the durability and performance of the alkaline water electrolysis diaphragm while maintaining good film resistance.
Smart Images

Figure 2025063577000002 
Figure 2025063577000003 
Figure 2025063577000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a diaphragm for alkaline water electrolysis and a method for producing the same. [Background technology]
[0002] Conventionally, a diaphragm for alkaline water electrolysis is known that contains inorganic particles, an organic resin, and a porous support. One of the issues to be addressed in such a diaphragm for alkaline water electrolysis is how to suppress the falling off of the inorganic particles (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-90909 Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made in consideration of the above-described circumstances, and an object of the present invention is to provide a diaphragm for alkaline water electrolysis capable of suppressing falling-off of inorganic particles. [Means for solving the problem]
[0005] That is, the present invention provides the following aspects. [1] A diaphragm for alkaline water electrolysis comprising a porous support and a porous membrane provided on one or both main surfaces of the porous support, the porous membrane comprising inorganic particles and an organic resin, the diaphragm further comprising a coating layer provided on one or both sides in the thickness direction of a main layer consisting of the porous support and the porous membrane, the coating layer comprising a polymer having an acid group. [2] The diaphragm for alkaline water electrolysis according to [1] above, wherein the polymer has a carboxy group. [3] The diaphragm for alkaline water electrolysis according to [1] or [2] above, wherein the coating layer comprises a coating layer-forming composition comprising the polymer and a crosslinking agent. [4] The diaphragm for alkaline water electrolysis according to any of [1] to [3], wherein the coating layer contains the inorganic particles only on the main layer side. [5] The diaphragm for alkaline water electrolysis according to any of [1] to [4] above, wherein the coating layer has a thickness of 0.05 to 5.00 μm. [6] The diaphragm for alkaline water electrolysis according to any of [1] to [5] above, wherein the porous membrane is provided on only one main surface of the porous support. [7] The diaphragm for alkaline water electrolysis according to any of [1] to [5] above, wherein the porous membrane is provided on both main surfaces of the porous support. [8] The diaphragm for alkaline water electrolysis according to any of [1] to [7], wherein the inorganic particles comprise at least one selected from the group consisting of magnesium hydroxide, zirconium oxide, titanium oxide, and barium sulfate. [9] The diaphragm for alkaline water electrolysis according to any of [1] to [8], wherein the organic resin comprises at least one selected from the group consisting of polysulfone, polyethersulfone, and polyphenylsulfone.
[10] The diaphragm for alkaline water electrolysis according to any of [1] to [9], wherein the porous support is a nonwoven fabric, woven fabric, or mesh comprising at least one material selected from the group consisting of polypropylene, polyethylene, and polyphenylene sulfide.
[11] The membrane resistance is 0.10 to 1.00 Ω cm 2 The diaphragm for alkaline water electrolysis according to any one of the above [1] to
[10] ,
[12] A method for producing a diaphragm for alkaline water electrolysis according to any of the above [1] to
[11] , comprising the steps of: adhering a composition for forming a porous membrane, which contains inorganic particles and an organic resin, to a porous support; bringing the porous support into contact with a non-solvent to form a main layer; and adhering a composition for forming a coating layer, which contains a polymer having acid groups, to the main layer wetted with the non-solvent, and drying the composition to form a coating layer. Effect of the Invention
[0006] The diaphragm for alkaline water electrolysis of the present invention can suppress falling off of inorganic particles. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a backscattered electron image by FE-SEM of a cross section of a diaphragm for alkaline water electrolysis obtained in an example. [Diagram 2] FIG. 4 is a diagram showing a method for determining the thickness of a coating layer in an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention will be described in detail below. A combination of two or more of the individual preferred embodiments of the present invention described below is also a preferred embodiment of the present invention. In this description, a numerical range indicated as "X to Y" means "X or more and Y or less." For example, "30 to 1000 μm" means "30 μm or more and 1000 μm or less."
[0009] 1. Diaphragms for alkaline water electrolysis The diaphragm for alkaline water electrolysis of the present invention comprises a porous support and a porous membrane provided on one or both main surfaces of the porous support, the porous membrane containing inorganic particles and an organic resin, and is characterized in that it further comprises a coating layer provided on one or both sides in the thickness direction of a main layer consisting of the porous support and the porous membrane, the coating layer containing a polymer having an acid group.
[0010] In the diaphragm for alkaline water electrolysis of the present invention, a portion consisting of a porous support and a porous membrane is referred to as a main layer. The main layer may consist of a porous support and a porous membrane provided on only one main surface of the porous support, or may consist of a porous support and a porous membrane provided on both main surfaces of the porous support. In the main layer, part of the porous membrane may be impregnated into the porous support.
[0011] The diaphragm for alkaline water electrolysis of the present invention further comprises a coating layer containing a polymer having an acid group on one or both sides in the thickness direction of the main layer. The provision of such a specific coating layer can suppress the falling off of inorganic particles contained in the porous membrane. In addition, the diaphragm for alkaline water electrolysis of the present invention exhibits good membrane resistance.
[0012] It is presumed that the reason why the inorganic particles can be prevented from falling off is that the inorganic particles, which have basic properties, are held by bonding to the acid groups of the polymer contained in the coating layer.
[0013] The coating layer is provided on one or both sides in the thickness direction of the main layer. The coating layer may be provided on the porous support or on the porous membrane. More specifically, when the main layer is composed of a porous support and a porous membrane provided only on one main surface of the porous support, the coating layer may be provided on the porous support, on the porous membrane, or on both the porous support and the porous membrane. When the main layer is composed of a porous support and a porous membrane provided on both main surfaces of the porous support, the coating layer may be provided on one of the porous membranes, or on both of the porous membranes. The coating layer is preferably located on the outermost surface of the diaphragm for alkaline water electrolysis.
[0014] The coating layer may contain inorganic particles only on the side of the main layer. In other words, the coating layer may contain inorganic particles only at the boundary with the main layer. The inorganic particles are the same as the inorganic particles contained in the porous membrane.
[0015] The porous support, the porous membrane, and the coating layer constituting the diaphragm for alkaline water electrolysis will be described below.
[0016] (porous support) The porous support is a sheet-like porous body and serves as a support for the diaphragm for alkaline water electrolysis.
[0017] Examples of materials for the porous support include resins such as polyethylene, polypropylene, polysulfone, polyethersulfone, polyphenylsulfone, polyphenylene sulfide, polyketone, polyimide, polyetherimide, fluorine-based resin, etc. The porous support may contain only one type of such resin, or may contain two or more types.
[0018] From the viewpoint of heat resistance and alkali resistance, the porous support preferably contains at least one selected from the group consisting of polypropylene, polyethylene and polyphenylene sulfide, more preferably at least one selected from the group consisting of polypropylene and polyphenylene sulfide. The total content of polypropylene, polyethylene and polyphenylene sulfide in the porous support is preferably 70 mass% or more, more preferably 90 mass% or more.
[0019] Examples of the form of the porous support include nonwoven fabric, woven fabric, mesh, porous membrane, mixed fabric of nonwoven fabric and woven fabric, etc. The porous support is preferably nonwoven fabric, woven fabric or mesh, more preferably nonwoven fabric or mesh.
[0020] Therefore, the porous support is preferably a nonwoven fabric, a woven fabric, or a mesh containing at least one material selected from the group consisting of polypropylene, polyethylene, and polyphenylene sulfide.
[0021] The thickness of the porous support is not particularly limited, but is preferably 30 to 1000 μm, and more preferably 50 to 400 μm.
[0022] The mass of the porous support is not particularly limited, but is preferably 20 to 200 g / m 2 It is preferable that the thickness is 40 to 150 g / m 2 It is more preferable that:
[0023] (Porous membrane) The porous membrane comprises inorganic particles and an organic resin.
[0024] Examples of the inorganic particles include hydroxides or oxides of magnesium, zirconium, titanium, zinc, aluminum, tantalum, etc., sulfates of calcium, barium, lead, strontium, etc., nitrides of titanium, zirconium, hafnium, etc., carbides of titanium, zirconium, hafnium, etc. The inorganic particles may contain only one type of such inorganic particles or may contain two or more types.
[0025] The inorganic particles preferably have basic properties, and from this viewpoint, they preferably contain at least one type selected from the group consisting of magnesium hydroxide, zirconium oxide, titanium oxide, and barium sulfate, and more preferably contain at least one type selected from the group consisting of magnesium hydroxide and zirconium oxide.
[0026] The inorganic particles may be surface-treated, for example, by known surface treatments using a silane coupling agent, stearic acid, oleic acid, phosphoric ester, or the like.
[0027] The shape of the inorganic particles is not particularly limited, and may be granular, granular, plate-like, fibrous, amorphous, or the like.
[0028] The average particle size of the inorganic particles is not particularly limited, but is preferably 0.01 to 1.50 μm, more preferably 0.10 to 1.00 μm, and even more preferably 0.20 to 0.50 μm. The average particle size is a volume average particle size (D50) determined by particle size distribution measurement by a laser diffraction method, and specifically, can be determined by the method described in the examples below.
[0029] The aspect ratio of the inorganic particles is not particularly limited, but is preferably 2.0 to 8.0, more preferably 2.5 to 7.0, and even more preferably 3.0 to 6.0. The aspect ratio is the ratio of the longest diameter (a) to the shortest diameter (b) [(a) / (b)], and can be determined by observing the inorganic particles with a SEM and using the average value of any 10 inorganic particles in the obtained image.
[0030] The specific surface area of the inorganic particles is not particularly limited, but is preferably 5 to 35 m 2 / g, and 5.5 to 25m 2 / g is more preferable, and 6 to 20m 2 / g is more preferable. The specific surface area can be determined by measurement using a BET specific surface area meter. Specifically, it can be determined by the method described in the examples below.
[0031] The content of the inorganic particles in the porous membrane is not particularly limited, but is preferably 60 to 95% by mass, more preferably 65 to 92% by mass, and further preferably 75 to 90% by mass.
[0032] Examples of the organic resin include fluorine-based resins such as ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride, polyvinyl fluoride, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polychlorotrifluoroethylene, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer, etc.; olefin-based resins such as polyethylene, polypropylene, polybutene, polymethylpentene, etc.; aromatic hydrocarbon-based resins such as polyethylene terephthalate, polybutylene terephthalate, polybutylene naphthalate, polystyrene, polysulfone, polyethersulfone, polyphenylene sulfide, polyphenylsulfone, polyarylate, polyetherimide, polyimide, polyamideimide, etc. The organic resin may contain only one type of such resin, or may contain two or more types.
[0033] From the viewpoint of heat resistance and alkali resistance, the organic resin preferably contains at least one selected from the group consisting of polysulfone, polyethersulfone and polyphenylsulfone, and more preferably contains polysulfone.
[0034] The content of the organic resin in the porous membrane is not particularly limited, but is preferably 5 to 40% by mass, more preferably 8 to 35% by mass, and further preferably 10 to 25% by mass.
[0035] The thickness of the porous membrane is not particularly limited, but is preferably 5 to 500 μm, more preferably 10 to 200 μm, and even more preferably 20 to 100 μm. When the porous membranes are provided on both main surfaces of the porous support, each of them preferably has the above-mentioned thickness.
[0036] (covering layer) The coating layer contains a polymer having an acid group. Examples of the acid group include a carboxy group, a phenolic hydroxyl group, a carboxylic anhydride group, a phosphoric acid group, and a sulfonic acid group. The polymer preferably has a carboxy group from the viewpoint of further suppressing the dropping of the inorganic particles and from the viewpoint of improving the mechanical strength of the coating layer.
[0037] The polymer is obtained by polymerizing a monomer component including a monomer having an acid group. Specific examples of the monomer having an acid group include unsaturated monocarboxylic acid (e.g., (meth)acrylic acid, crotonic acid, etc.), unsaturated dicarboxylic acid (e.g., maleic acid, fumaric acid, etc.), acid anhydride (e.g., maleic anhydride, itaconic anhydride, etc.), monomer having sulfonic acid (e.g., vinyl sulfonic acid, styrene sulfonic acid, etc.), monomer having a phosphoric acid group {e.g., phosphoric acid mono- or triester [e.g., mono(2-methacryloyloxyethyl)phosphate, mono(2-acryloyloxyethyl)phosphate, 2-(meth)acryloyloxypropylphosphate]}, etc. The monomer having an acid group may contain only one type of such monomer, or may contain two or more types.
[0038] In this specification, "(meth)acrylic acid" means "acrylic acid" and "methacrylic acid", "(meth)acrylate" means "acrylate" and "methacrylate", and "(meth)acryloyl" means "acryloyl" and "methacryloyl".
[0039] The monomer component used in the synthesis of the polymer may contain other monomers in addition to the above-mentioned monomers having an acid group. The other monomers are not particularly limited, and examples thereof include (meth)acrylic acid alkyl esters, hydroxyl group-containing monomers, (poly)oxyalkylene group-containing monomers, silane group-containing monomers, nitrogen atom-containing monomers, oxo group-containing monomers, fluorine atom-containing monomers, and epoxy group-containing monomers. In particular, from the viewpoint of improving the mechanical strength of the coating layer, the other monomers preferably contain at least one selected from the group consisting of (meth)acrylic acid alkyl esters, hydroxyl group-containing monomers, and (poly)oxyalkylene group-containing monomers, and more preferably contain (meth)acrylic acid alkyl esters.
[0040] Examples of the (meth)acrylic acid alkyl esters include (meth)acrylic acid esters having a linear alkyl group, (meth)acrylic acid esters having a branched alkyl group, and (meth)acrylic acid esters having a cyclic alkyl group.
[0041] Examples of the (meth)acrylic acid esters having the linear alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, behenyl (meth)acrylate, methoxyethyl (meth)acrylate, ethyl carbitol (meth)acrylate, ethoxy polyethylene glycol (meth)acrylate, aminoethyl (meth)acrylate, etc. Among them, from the viewpoint of improving the mechanical strength of the coating layer, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and butyl (meth)acrylate are preferred.
[0042] Examples of the (meth)acrylic acid esters having the branched alkyl group include isopropyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, neopentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isodecyl (meth)acrylate, isostearyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, methoxytripropylene glycol (meth)acrylate, etc. Among these, from the viewpoint of improving the mechanical strength of the coating layer, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, neopentyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred.
[0043] Examples of the (meth)acrylic acid esters having a cyclic alkyl group include cyclopropyl (meth)acrylate, cyclobutyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, etc. Among them, cyclohexyl (meth)acrylate is preferred from the viewpoint of improving the mechanical strength of the coating layer.
[0044] The above (meth)acrylic acid alkyl esters preferably have 1 to 40 carbon atoms.
[0045] Examples of the hydroxyl group-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, etc. The carbon number of the hydroxyl group-containing monomer is preferably 1 to 20.
[0046] Examples of the (poly)oxyalkylene group-containing monomer include (poly)alkylene glycol mono(meth)acrylates such as (poly)ethylene glycol mono(meth)acrylate, (poly)propylene glycol mono(meth)acrylate, (poly)butylene glycol mono(meth)acrylate, (poly)ethylene glycol (poly)propylene glycol mono(meth)acrylate, (poly)ethylene glycol (poly)butylene glycol mono(meth)acrylate, (poly)propylene glycol (poly)butylene glycol mono(meth)acrylate, and (poly)ethylene glycol (poly)propylene glycol (poly)butylene glycol mono(meth)acrylate; (methoxy)polyethylene glycol (meth)acrylate, (methoxy)polypropylene glycol (meth)acrylate, (methoxy)polybutylene glycol (meth)acrylate, (methoxy)polyethylene glycol polypropylene glycol (meth)acrylate, and (methoxy)polyethylene glycol polybutylene. Examples of the alkylene glycol (meth)acrylate include alkoxy (poly)alkylene glycol (meth)acrylates such as glycol (meth)acrylate, (methoxy)polypropylene glycol polybutylene glycol (meth)acrylate, (methoxy)polyethylene glycol polypropylene glycol polybutylene glycol (meth)acrylate, (ethoxy)polyethylene glycol (meth)acrylate, (ethoxy)polypropylene glycol (meth)acrylate, (ethoxy)polybutylene glycol (meth)acrylate, (ethoxy)polyethylene glycol polybutylene glycol (meth)acrylate, (ethoxy)polyethylene glycol polybutylene glycol (meth)acrylate, (ethoxy)polyethylene glycol polybutylene glycol (meth)acrylate, (ethoxy)polyethylene glycol polybutylene glycol (meth)acrylate, stearyl polyethylene glycol (meth)acrylate, and cyclohexyl polyethylene glycol (meth)acrylate. The carbon number of the (poly)oxyalkylene group-containing monomer is preferably 1 to 200.
[0047] From the viewpoint of further suppressing the dropping off of inorganic particles and improving the film resistance, the polymer preferably contains 5 to 50 mass% of the structural units derived from the monomer having an acid group, relative to 100 mass% of all structural units (i.e., the total of the structural units derived from the monomer having an acid group and the structural units derived from the other monomers).
[0048] The polymer preferably contains 50 to 95% by mass of structural units derived from the other monomers, relative to 100% by mass of all structural units.
[0049] The polymer preferably contains 50 to 95% by mass of structural units derived from the (meth)acrylic acid alkyl esters, relative to 100% by mass of all structural units.
[0050] The polymer preferably contains 50 to 95% by mass of structural units derived from the hydroxyl group-containing monomer, relative to 100% by mass of all structural units.
[0051] The above polymer preferably contains 50 to 95% by mass of structural units derived from the above (poly)oxyalkylene group-containing monomer, relative to 100% by mass of all structural units.
[0052] The polymer may be dissolved in a solvent, but is preferably in the form of an emulsion (emulsion particles). In the form of an emulsion, a coating layer that can effectively suppress the dropping of inorganic particles with a relatively small thickness can be formed.
[0053] The polymer can be obtained by polymerizing the monomer components including the above-mentioned monomers. The polymerization method may be appropriately selected, but emulsion polymerization is preferable.
[0054] Examples of the method for emulsion polymerizing the monomer components include a method in which an emulsifier is dissolved in a medium such as water and a water-soluble organic solvent, for example, a lower alcohol, for example, methanol, or in a medium such as water, and the monomer components and a polymerization initiator are added dropwise under stirring; and a method in which a monomer component that has been emulsified in advance using an emulsifier and water is added dropwise to water or an aqueous medium.
[0055] When emulsion-polymerizing the monomer component, the emulsion polymerization may be carried out after mixing the monomer component, the emulsifier, and the medium, or the monomer component, the emulsifier, and the medium are emulsified by stirring to prepare a pre-emulsion, and then the emulsion polymerization may be carried out, or at least one of the monomer component, the emulsifier, and the medium and the remaining pre-emulsion may be mixed to carry out the emulsion polymerization. The monomer component, the emulsifier, and the medium may each be added all at once, added in portions, or added dropwise continuously.
[0056] The method of forming emulsion particles by emulsion polymerization may be a method of adding a part of a monomer component to an aqueous medium such as water to form seed particles, and then adding the remaining monomer component to form emulsion particles, or a method of forming emulsion particles by multi-stage polymerization of two or more stages, in which a core portion is formed by emulsion polymerizing a monomer component in an aqueous medium in the presence of an emulsifier, and then a shell portion is formed by further emulsion polymerizing a monomer component different from the core portion into the emulsion containing the core portion.
[0057] Examples of the emulsifier include anionic emulsifiers such as polyoxyethylene alkyl ether sulfate, allyloxyalkyl polyoxyethylene sulfate, and polyoxyalkylene alkenyl ether ammonium sulfate, nonionic emulsifiers, cationic emulsifiers, amphoteric emulsifiers, and polymeric emulsifiers. Only one type of emulsifier may be used, or two or more types may be used in combination.
[0058] The amount of the emulsifier used may be appropriately selected, but is preferably 0.1 to 10 parts by mass per 100 parts by mass of the monomer component.
[0059] The medium includes water or an aqueous medium, and the aqueous medium includes a mixed solvent of water and a water-soluble organic solvent such as a lower alcohol, e.g., methanol.
[0060] The amount of the medium used may be appropriately selected, but is preferably 50 to 500 parts by mass per 100 parts by mass of the monomer component.
[0061] Examples of the polymerization initiator used in the polymerization include azo compounds such as azobisisobutyronitrile, 2,2-azobis(2-methylbutyronitrile), 2,2-azobis(2,4-dimethylvaleronitrile), 2,2-azobis(2-diaminopropane) hydrochloride, 4,4-azobis(4-cyanovaleric acid), and 2,2-azobis(2-methylpropionamidine); persulfates such as potassium persulfate; and peroxides such as hydrogen peroxide, benzoyl peroxide, parachlorobenzoyl peroxide, lauroyl peroxide, and ammonium peroxide. Only one type of polymerization initiator may be used, or two or more types may be used in combination.
[0062] The amount of the polymerization initiator used may be appropriately selected, but is preferably 0.05 to 1 part by mass with respect to 100 parts by mass of the monomer component.
[0063] The polymerization reaction may be carried out, as necessary, in the presence of a reducing agent (e.g., sodium hydrogen sulfite), a decomposing agent for the polymerization initiator (e.g., a transition metal salt such as ferrous sulfate), a chain transfer agent (e.g., a compound having a thiol group such as tert-dodecyl mercaptan), a pH buffer, a chelating agent, etc.
[0064] The polymerization may be carried out in an air atmosphere or in an inert gas atmosphere such as nitrogen or argon.
[0065] The polymerization temperature may be appropriately selected, and is preferably, for example, from 50 to 100° C. The polymerization temperature may be constant or may be changed during the polymerization reaction.
[0066] The polymerization time may be appropriately selected, but is preferably, for example, 1 hour or more.
[0067] The average particle size of the polymer emulsion particles is preferably 20 to 500 nm from the viewpoint of better suppressing the dropping off of the inorganic particles. The average particle size is a volume average particle size measured using a particle size distribution measuring device by dynamic light scattering (for example, NICOMP Model 380, manufactured by Particle Size Systems, Inc.).
[0068] The coating layer can be formed using a coating layer-forming composition containing the polymer. The content of the polymer may be appropriately set depending on the thickness of the coating layer to be formed, and is preferably 0.5 to 30% by mass, more preferably 1 to 20% by mass, and even more preferably 2 to 10% by mass, based on 100% by mass of the coating layer-forming composition.
[0069] The coating layer-forming composition preferably further contains a crosslinking agent. By containing a crosslinking agent, it is possible to further suppress the inorganic particles from falling off. In addition, it is possible to suppress an increase in the film resistance.
[0070] The crosslinking agent may be a compound having a plurality of groups that react with an acid group. Examples of the group that reacts with an acid group include an oxazoline group, a carbodiimide group, an epoxy group, an amino group, an isocyanate group, and a silane group. From the viewpoint of good reactivity with an acid group, the group that reacts with an acid group preferably includes at least one selected from the group consisting of an oxazoline group and a carbodiimide group, and more preferably includes an oxazoline group.
[0071] Examples of compounds having a plurality of oxazoline groups include 2,2'-bis(2-oxazoline), 2,2'-methylene-bis(2-oxazoline), 2,2'-ethylene-bis(2-oxazoline), 2,2'-trimethylene-bis(2-oxazoline), 2,2'-tetramethylene-bis(2-oxazoline), 2,2'-hexamethylene-bis(2-oxazoline), and 2,2'-octamethylene-bis(2-oxazoline). Examples of the oxazolinyl cyclohexane sulfide include 2,2'-ethylene-bis(4,4'-dimethyl-2-oxazoline), 2,2'-p-phenylene-bis(2-oxazoline), 2,2'-m-phenylene-bis(2-oxazoline), 2,2'-m-phenylene-bis(4,4'-dimethyl-2-oxazoline), bis(2-oxazolinylcyclohexane)sulfide, and bis(2-oxazolinylnorbornane)sulfide. Examples of the oxazolinyl cyclohexane sulfide include commercially available products such as Epocross (registered trademark) WS-500, Epocross WS-700, Epocross K-2010, Epocross K-2020, and Epocross K-2030 manufactured by Nippon Shokubai Co., Ltd.
[0072] Examples of compounds having multiple carbodiimide groups include commercially available products such as Carbodilite (registered trademark) SV-02 manufactured by Nisshinbo Chemical Inc. and Carbodista (registered trademark) manufactured by Teijin Limited.
[0073] The content of the crosslinking agent is preferably 1 to 10 parts by mass with respect to 100 parts by mass of the polymer.
[0074] The coating layer forming composition may further contain a solvent. The solvent is not particularly limited, but is preferably water or an aqueous solvent in that the polymer can be contained in the form of an emulsion. The aqueous solvent may be a water-soluble organic solvent such as a lower alcohol such as methanol or ethanol, or a mixed solvent of the water-soluble organic solvent and water.
[0075] A method for forming a coating layer using the coating layer-forming composition will be described in the method for producing a diaphragm for alkaline water electrolysis described later.
[0076] The thickness of the coating layer is not particularly limited, but is preferably 0.05 to 5.00 μm from the viewpoint of further suppressing the dropping of inorganic particles and improving the mechanical strength of the coating layer. The thickness of the coating layer can be determined by the method described in the examples below.
[0077] The thickness of the diaphragm for alkaline water electrolysis is not particularly limited, but from the viewpoint of improving the mechanical strength of the diaphragm for alkaline water electrolysis, it is preferably 50 to 1200 μm, more preferably 100 to 600 μm, and even more preferably 150 to 500 μm. The thickness of the diaphragm for alkaline water electrolysis can be determined by the method described in the examples below.
[0078] The membrane resistance of the diaphragm for alkaline water electrolysis is not particularly limited, but is preferably 0.10 to 1.00 Ω cm 2 Preferably, the resistance is 0.10 to 0.50 Ωcm. 2 More preferably, the resistance is 0.10 to 0.30 Ωcm. 2 The membrane resistance can be determined by the method described in the Examples below.
[0079] 2. Manufacturing method of diaphragm for alkaline water electrolysis The method for producing the diaphragm for alkaline water electrolysis of the present invention preferably includes the following steps (1) to (3). (1) A step of attaching a composition for forming a porous membrane containing inorganic particles and an organic resin to a porous support (2) contacting the porous support with a non-solvent to form a main layer; (3) A step of applying a coating layer-forming composition containing a polymer having an acid group to the main layer in a state wetted with the non-solvent, and then drying the composition to form a coating layer.
[0080] Process (1) Step (1) is a step of attaching a porous membrane-forming composition containing inorganic particles and an organic resin to a porous support. The porous membrane-forming composition is prepared by mixing the organic resin, inorganic particles, and a solvent. For example, a dispersion liquid (slurry) in which inorganic particles are dispersed in a solvent and a resin solution in which an organic resin is dissolved in a solvent may be prepared, and then the two may be mixed.
[0081] The solvent is not particularly limited as long as it has the property of dissolving the organic resin, and examples thereof include N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethylsulfoxide, etc. Only one type of solvent may be used, or two or more types may be used in combination.
[0082] The content of the inorganic particles in the composition for forming a porous membrane is not particularly limited, but is preferably 20 to 50% by mass.
[0083] The content of the organic resin in the composition for forming a porous membrane is not particularly limited, but is preferably 5 to 50% by mass.
[0084] The porous membrane forming composition may further contain a dispersant. Examples of the dispersant include water-soluble polymers such as polyethylene glycol, ethylene glycol, polyacrylic acid, and dextran; cationic surfactants; anionic surfactants; and pigment dispersants having functional groups such as carboxyl groups, phosphate groups, and sulfonic acid groups. The amount of the dispersant used is preferably 0.1 to 10 parts by mass relative to 100 parts by mass of the inorganic particles.
[0085] The porous membrane forming composition may further contain an additive. Examples of the additive include polyethylene oxide, polyvinylpyrrolidone, polyethyleneimine, glycerin, sugars, chlorides such as calcium chloride, magnesium chloride, and lithium chloride, and 2-ethyl-1-hexanol. The amount of the additive used is preferably 0.1 to 20 parts by mass relative to 100 parts by mass of the inorganic particles.
[0086] The composition for forming a porous membrane can be prepared using a known mixing means such as a mixer, a bead mill, a ball mill, a jet mill, a disper, a sand mill, a roll mill, a pot mill, or a paint shaker.
[0087] The method for attaching the composition for forming a porous membrane to the porous support is not particularly limited, and known methods such as a coating method using an apparatus such as die coating, spin coating, gravure coating, curtain coating, spray, applicator, coater, or the like, or a dipping method can be used.
[0088] The amount of the composition for forming a porous membrane adhered is not particularly limited as long as the porous membrane is formed on one or both main surfaces of the porous support, but it is preferable that the composition for forming a porous membrane is applied in an amount that allows the entire porous support to be impregnated with the composition for forming a porous membrane.
[0089] Process (2) Step (2) is a step of contacting the porous support to which the composition for forming a porous film is attached in step (1) with a non-solvent to form a main layer. By contacting the porous support to which the composition for forming a porous film is attached with a non-solvent, the non-solvent diffuses into the attached composition for forming a porous film, and the organic resin that is not dissolved in the non-solvent solidifies. Meanwhile, the solvent in the composition for forming a porous film that can be dissolved in the non-solvent is dissolved. By the occurrence of such phase separation, a porous film having holes is formed, and a main layer consisting of the porous support and the porous film is formed.
[0090] The non-solvent is not particularly limited as long as it has the property of not substantially dissolving the organic resin, and examples thereof include water (ion-exchanged water); lower alcohols such as methanol, ethanol, and propyl alcohol; or mixed solvents thereof. The non-solvent may contain a small amount of the same solvent as the solvent contained in the composition for forming a porous membrane, in addition to the above-mentioned components.
[0091] Examples of the method for contacting the porous support with the non-solvent include a method in which the porous support is immersed in the non-solvent (coagulation bath).
[0092] The temperature of the non-solvent when the porous support is brought into contact with the non-solvent is preferably 5 to 50°C.
[0093] Process (3) Step (3) is a step of attaching a coating layer forming composition containing a polymer having an acid group to the body layer in a state wet with the non-solvent, and then drying to form a coating layer. In step (3), the coating layer forming composition containing a polymer having an acid group is attached to the body layer in a state wet with the non-solvent. In this way, after contacting with the non-solvent in step (2), the non-solvent is not removed, and the coating layer forming composition is attached to the body layer in a state still wet with the non-solvent, so that the coating layer forming composition does not penetrate into the body layer (especially the porous membrane), the pores of the porous membrane are maintained, and a coating layer with a relatively thin thickness can be formed well.
[0094] Examples of the above-mentioned polymer having an acid group and the composition for forming a coating layer containing the above-mentioned polymer include the polymer having an acid group and the composition for forming a coating layer described in the above-mentioned section on the coating layer.
[0095] The method for adhering the composition for forming a covering layer can be, for example, the same method as the method for adhering the composition for forming a porous membrane in the above-mentioned step (1).
[0096] The amount of the coating layer-forming composition to be applied is not particularly limited, and may be appropriately adjusted so that a coating layer of desired thickness is formed.
[0097] After the coating layer-forming composition is applied, it is dried to form a coating layer. The drying method is not particularly limited and can be performed by a known method. The drying temperature is preferably 60 to 150° C. The drying time is preferably 1 to 60 minutes.
[0098] In this way, the diaphragm for alkaline water electrolysis of the present invention can be efficiently produced by the above-mentioned steps (1) to (3). The method for producing the diaphragm for alkaline water electrolysis may also include other known steps, as necessary.
[0099] The diaphragm for alkaline water electrolysis of the present invention can suppress falling-off of inorganic particles. The diaphragm for alkaline water electrolysis can be suitably used as a diaphragm for water electrolysis using an alkaline aqueous solution as an electrolyte. EXAMPLES
[0100] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0101] In the present examples, the conditions for measuring various physical properties are as follows: <Average particle size of inorganic particles> Inorganic particles and a 0.2% by mass aqueous solution of sodium hexametaphosphate were mixed to prepare an inorganic particle dispersion. After dispersing the inorganic particle dispersion using an ultrasonic cleaner, the particle size distribution was measured using a laser diffraction / scattering particle size distribution analyzer (product name: LA-950, manufactured by Horiba, Ltd.) by adjusting the transmittance of the red laser to 90-98% and the transmittance of the blue laser to 85-92%. The median diameter (d50) in the volume-based particle size distribution was taken as the average particle diameter (μm) of the inorganic particles.
[0102] <Specific surface area of inorganic particles> 1 g of inorganic particles was placed in a cell, and degassed at 200°C while circulating nitrogen gas through the cell. While circulating nitrogen gas through the cell, the cell was immersed in liquid nitrogen and nitrogen gas was adsorbed onto the inorganic particles at -196°C. The cell was kept at room temperature (25-27°C), and the amount of nitrogen gas desorbed was measured to determine the specific surface area by the BET method. A BET specific surface area meter (Macsorb HM model-1210, manufactured by Mountec Co., Ltd.) was used as the measuring device. This measurement was performed three times, and the average of each measurement result was taken as the specific surface area (m2) of the inorganic particles. 2 / g).
[0103] <Thickness of porous support and thickness of diaphragm for alkaline water electrolysis> The thickness of the porous support and the thickness of the diaphragm for alkaline water electrolysis were measured using a digimatic micrometer (coolant-proof micrometer MDC-PXT manufactured by Mitutoyo Corporation). This measurement was performed at any 10 points, and the average values of the measurement results were defined as the thickness of the porous support and the thickness of the diaphragm for alkaline water electrolysis.
[0104] <Coating layer thickness> The alkaline water electrolysis diaphragm was positioned so that the coating layer was located on the upper side, and a backscattered electron image was obtained using a field emission scanning electron microscope (FE-SEM). The magnification was 10,000 times. In the backscattered electron image, inorganic particles are shown in white, organic resin and coating layer are shown in gray, and voids and background are shown in black. Since inorganic particles are dispersed in the organic resin, the coating layer and the organic resin are distinguished by the presence or absence of inorganic particles shown in white. Using the image analysis software "Image Pro Premier" (manufactured by Media Cybernetics), the boundary between the coating layer and the porous membrane was determined visually, and a boundary line A between the coating layer and the porous membrane was drawn as shown in Figure 2. A perpendicular line B was drawn from the boundary line A, and an intersection C between the perpendicular line B and the upper surface of the coating layer was identified. The length from the boundary line A to the intersection C was measured. This measurement was performed for any five points on the boundary line A, and the average value of each measurement result was taken as the thickness of the coating layer. The boundary between the coating layer shown in gray and the background shown in black was taken as the upper surface of the coating layer.
[0105] <Particle release resistance test> The alkaline water electrolysis diaphragm was cut to 100 mmφ and fixed to an acrylic plate of 100 mmφ using double-sided tape. In Examples 1 to 6, 8 and Comparative Example 1, the main surface on the porous support side was fixed to the acrylic plate. In Example 7, the main surface on the porous membrane side was fixed to the acrylic plate. The alkaline water electrolysis diaphragm was immersed in ion-exchanged water for 1 hour. A 50-mesh (JIS mesh) wire mesh was cut to 100 mmφ and fixed to a stirrer using double-sided tape. The acrylic plate, alkaline water electrolysis diaphragm, mesh, and stirrer were placed in a glass petri dish in the following order from the bottom. Ion-exchanged water was poured in until the alkaline water electrolysis diaphragm was immersed. The mesh was rotated at 100 rpm for 2 hours using a magnetic stirrer. The fallen material in the glass petri dish was collected and its mass was measured.
[0106] <Membrane resistance of diaphragms for alkaline water electrolysis> Two measurement samples were cut out from the diaphragm for alkaline water electrolysis. The measurement samples were immersed in a 30% by mass aqueous potassium hydroxide solution overnight. The diaphragm for alkaline water electrolysis was installed in a cell having the cell configuration described below, and the cell was then allowed to stand in a thermostatic bath at 25°C for 30 minutes. Thereafter, AC impedance measurement was performed under the measurement conditions described below to obtain an intercept component (Ra). AC impedance measurement was also performed without the diaphragm for alkaline water electrolysis to obtain an intercept component (Rb). The membrane resistance was then calculated according to the following formula. This measurement was performed on two measurement samples, and the average value of the measurement results was taken as the membrane resistance of the diaphragm for alkaline water electrolysis. [Membrane resistance (Ωcm 2 )]=(Ra-Rb)×1.77 (Measurement conditions) Cell configuration Working electrode: Ni plate Counter electrode: Ni plate Electrolyte: 30% by weight potassium hydroxide aqueous solution Effective measurement area: 1.77cm 2 AC impedance measurement conditions Applied voltage: 10mV vs. open circuit voltage Frequency range: 100kHz~100Hz
[0107] <Example 1> (1. Preparation of Inorganic Particle Dispersion) Magnesium hydroxide particles (plate-shaped, average particle size 0.25 μm, specific surface area 20 m 2 Magnesium hydroxide dispersion was obtained by removing the zirconia beads.
[0108] (2. Preparation of Porous Membrane Forming Composition) To 200 parts by mass of magnesium hydroxide dispersion, 100 parts by mass of polysulfone solution in which polysulfone (BASF: Ultrason S3010) was dissolved in N-methyl-2-pyrrolidone (Mitsubishi Chemical) at a concentration of 35% by mass, 40 parts by mass of 2-ethyl-1-hexanol (FUJIFILM Wako Pure Chemical Industries, Ltd.), 7.0 parts by mass of polyvinylpyrrolidone (Nippon Shokubai: K-30), and 1.5 parts by mass of polyethyleneimine (Nippon Shokubai: SP-018) were added. N-methyl-2-pyrrolidone (Mitsubishi Chemical) was added to make the total concentration of magnesium hydroxide and polysulfone 35% by mass. The mixture was stirred under the conditions of 27°C / 30 minutes / 1000 rpm using a planetary centrifugal mixer (Thinky: Awatori Rentaro ARE-500). In this way, a composition for forming a porous membrane was obtained.
[0109] (3. Formation of the main layer) Polyphenylene sulfide nonwoven fabric (film thickness 130μm, basis weight 60g / m 2 A composition for forming a porous membrane was applied to one surface of the substrate using an applicator (application amount: 30 mg / cm 2 ). At this time, the composition for forming a porous membrane was allowed to penetrate to the opposite surface of the nonwoven fabric. The nonwoven fabric impregnated with the composition for forming a porous membrane was placed in a water bath at 27°C for 3 minutes to obtain a main layer including a porous membrane containing magnesium hydroxide and polysulfone, and a nonwoven fabric. This main layer was left wet with water without being dried.
[0110] (4. Preparation of composition for forming coating layer) A flask equipped with a dropping funnel, a stirrer, a nitrogen gas inlet tube, a thermometer, and a reflux condenser was charged with 453 parts by mass of deionized water and 64 parts by mass of a 20% by mass aqueous solution of an emulsifier (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name: Hitenol (registered trademark) LA-10).
[0111] A pre-emulsion consisting of 30 parts by mass of deionized water, 32 parts by mass of a 20% by mass aqueous solution of an emulsifier (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name: Hitenol LA-10), 340 parts by mass of ethyl acrylate, 250 parts by mass of methacrylic acid, and 500 parts by mass of a 10% by mass aqueous solution of polyalkylene glycol (90) monomethacrylate (manufactured by NOF Corporation: Blemmer (registered trademark) PSE-1300) was prepared in a dropping funnel, and 73 parts by mass of the pre-emulsion was added to the flask. The temperature was raised to 72°C while slowly blowing in nitrogen gas, and polymerization was initiated by adding 2.3 parts by mass of a 5.0% by mass aqueous solution of sodium hydrogensulfite and 8 parts by mass of a 1.0% by mass aqueous solution of ammonium persulfate to the flask.
[0112] The remainder of the pre-emulsion and 144 parts by mass of a 1.0% by mass aqueous solution of ammonium persulfate were added dropwise to the flask at a uniform pace over 120 minutes. After the addition was completed, the contents of the flask were maintained at 72° C. for 60 minutes and then cooled to terminate the polymerization reaction.
[0113] The resulting reaction liquid was cooled to room temperature and then filtered through a 300 mesh (JIS mesh, the same applies below) wire screen to obtain a coating layer-forming composition 1 having a solid content of 29.6 mass %.
[0114] (5. Formation of coating layer) The coating layer-forming composition 1 was diluted to give a 2% by mass aqueous solution, which was stored in a tray. The surface of the porous membrane wetted with water was brought into contact with this aqueous solution and then dried at 130°C for 10 minutes. In this manner, a diaphragm 1 for alkaline water electrolysis was obtained in which a coating layer was formed on the main surface of the porous membrane. The diaphragm 1 for alkaline water electrolysis was subjected to measurement of the overall thickness, measurement of the thickness of the coating layer, a particle shedding resistance test, and measurement of the membrane resistance. The results are shown in Table 1.
[0115] <Examples 2 to 4> Diaphragms for alkaline water electrolysis 2 to 4 were produced in the same manner as in Example 1, except that the thickness of the coating layer was adjusted by adjusting the types of inorganic particles and organic resin, and the concentration of the diluted coating layer-forming composition 1, as shown in Table 1. The obtained diaphragms for alkaline water electrolysis 2 to 4 were subjected to measurement of the overall thickness, measurement of the thickness of the coating layer, measurement of resistance to particle shedding, and measurement of membrane resistance. The results are shown in Table 1.
[0116] <Example 5> (1. Formation of the main layer) The main layer was formed in the same manner as in Example 1. (2. Preparation of Coating Layer-Forming Composition 2) 1500 parts by mass of deionized water was charged into a flask equipped with a dropping funnel, a stirrer, a nitrogen gas inlet tube, a thermometer and a reflux condenser. A pre-emulsion A consisting of 163 parts by mass of deionized water, 150 parts by mass of a 25% by mass aqueous solution of an emulsifier (manufactured by Adeka Reasoap (registered trademark) SR-10, manufactured by Adeka Co., Ltd.), 100 parts by mass of 2-ethylhexyl acrylate, 70 parts by mass of cyclohexyl methacrylate and 800 parts by mass of methyl methacrylate was prepared in the dropping funnel, 74 parts by mass of the pre-emulsion A was added to the flask, and the temperature was raised to 80° C. while slowly blowing in nitrogen gas, and 50 parts by mass of a 5% by mass aqueous solution of potassium persulfate was added to the flask to initiate polymerization.
[0117] The remaining portion of pre-emulsion A was added dropwise evenly into the flask over a period of 120 minutes. After completion of the addition, the contents of the flask were maintained at 80° C. for 60 minutes.
[0118] Subsequently, pre-emulsion B consisting of 163 parts by mass of deionized water, 150 parts by mass of a 25% aqueous solution of an emulsifier [ADEKA Corporation: ADEKA Reasoap SR-10], 400 parts by mass of 2-ethylhexyl acrylate, 100 parts by mass of butyl acrylate, 50 parts by mass of hydroxyethyl methacrylate, 400 parts by mass of methyl methacrylate, 5 parts by mass of acrylic acid, and 5 parts by mass of methacrylic acid, and 50 parts by mass of a 5% aqueous solution of potassium persulfate were added dropwise into the flask at a uniform pace over 120 minutes. After the dropwise addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and then 25% by mass of ammonia water was added to adjust the pH to 9, thereby completing the polymerization reaction.
[0119] The resulting reaction liquid was cooled to room temperature and then filtered through a 300 mesh wire screen to obtain a coating layer-forming composition 2 having a non-solid content of 50 mass %.
[0120] (3. Formation of coating layer) The coating layer forming composition 2 was diluted to a 0.5 mass% aqueous solution, which was stored in a tray. A crosslinking agent (Epocross WS-700, manufactured by Nippon Shokubai Co., Ltd.) was added thereto. The content of the crosslinking agent was 5 mass% relative to the solid content of the coating layer forming composition 2. The surface of the porous membrane wetted with water was brought into contact with this aqueous solution, and then dried under the conditions of 130°C / 10 minutes. In this manner, a diaphragm 5 for alkaline water electrolysis was obtained in which a coating layer was formed on the main surface of the porous membrane. The diaphragm 5 for alkaline water electrolysis was subjected to measurement of the overall thickness, measurement of the coating layer thickness, a particle shedding resistance test, and measurement of the membrane resistance. The results are shown in Table 1.
[0121] <Example 6> (1. Formation of the main layer) The main layer was formed in the same manner as in Example 2. (2. Preparation of Coating Layer-Forming Composition 3) A flask equipped with a dropping funnel, a stirrer, a nitrogen gas inlet tube, a thermometer, and a reflux condenser was charged with 1500 parts by mass of deionized water. A pre-emulsion C consisting of 163 parts by mass of deionized water, 150 parts by mass of a 25% by mass aqueous solution of an emulsifier (ADEKA Corporation: Adeka Reasoap SR-10), 7 parts by mass of 2-ethylhexyl acrylate, 7 parts by mass of cyclohexyl methacrylate, 550 parts by mass of methyl methacrylate, 5 parts by mass of tert-butyl methacrylate, and 10 parts by mass of butyl acrylate was prepared in the dropping funnel, and 74 parts by mass of the pre-emulsion C was added to the flask, and the temperature was raised to 80° C. while slowly blowing in nitrogen gas. A polymerization reaction was started by adding 50 parts by mass of a 5% by mass aqueous solution of potassium persulfate to the flask.
[0122] The remainder of pre-emulsion C, 10 parts by mass of a 5% by mass aqueous solution of potassium persulfate, and 10 parts by mass of a 2.5% by mass aqueous solution of sodium hydrogen sulfite were added dropwise to the flask at a uniform pace over 120 minutes. After completion of the addition, the contents of the flask were maintained at 80° C. for 60 minutes.
[0123] Next, pre-emulsion D consisting of 163 parts by mass of deionized water, 150 parts by mass of a 25% by mass aqueous solution of an emulsifier (ADEKA Corporation: ADEKA REASOAP SR-10), 540 parts by mass of 2-ethylhexyl acrylate, 100 parts by mass of butyl acrylate, 400 parts by mass of methyl methacrylate, and 6 parts by mass of acrylic acid, and 10 parts by mass of a 5% by mass aqueous solution of potassium persulfate were added dropwise into the flask at a uniform pace over 120 minutes. After the addition was completed, the contents of the flask were maintained at 80°C for 60 minutes, and then 8 parts by mass of 25% by mass aqueous ammonia were added.
[0124] Subsequently, a pre-emulsion for third-stage dropping, consisting of 163 parts by mass of deionized water, 150 parts by mass of a 25% by mass aqueous solution of an emulsifier [ADEKA Corporation: ADEKA REASOAP SR-10], 180 parts by mass of 2-ethylhexyl acrylate, 340 parts by mass of methyl methacrylate, 5 parts by mass of acrylic acid, and 50 parts by mass of hydroxyethyl methacrylate, and 10 parts by mass of a 5% by mass aqueous solution of potassium persulfate, were dropped into the flask at a uniform pace over 120 minutes. After the dropping was completed, the contents of the flask were maintained at 80°C for 60 minutes, and the pH was adjusted to 9 by adding 25% by mass aqueous ammonia, thereby completing the polymerization reaction.
[0125] The resulting reaction liquid was cooled to room temperature and then filtered through a 300 mesh wire screen to obtain a coating layer-forming composition 3 having a solid content of 50 mass %.
[0126] (3. Formation of coating layer) The coating layer forming composition 3 was diluted to a 1 mass% aqueous solution, which was stored in a tray. A crosslinking agent (Carbodilite SV-02, manufactured by Nisshinbo Chemical Inc.) was added thereto. The content of the crosslinking agent was 5 mass% based on the solid content of the coating layer forming composition 3. The surface of the porous membrane wetted with water was brought into contact with this aqueous solution, and then dried under conditions of 130°C / 10 minutes. In this manner, a diaphragm 6 for alkaline water electrolysis was obtained in which a coating layer was formed on the main surface of the porous membrane. The diaphragm 6 for alkaline water electrolysis was subjected to measurement of the overall thickness, measurement of the thickness of the coating layer, a particle shedding resistance test, and measurement of the membrane resistance. The results are shown in Table 1.
[0127] <Example 7> (1. Formation of the main layer) The main layer was formed in the same manner as in Example 3.
[0128] (2. Formation of coating layer) The coating layer forming composition 1 was diluted to a 3 mass% aqueous solution, which was stored in a tray. A crosslinking agent (Epocross WS-700, manufactured by Nippon Shokubai Co., Ltd.) was added thereto. The content of the crosslinking agent was 10 mass% relative to the solid content of the coating layer forming composition 1. The surface of the porous support wetted with water was brought into contact with this aqueous solution, and then dried under conditions of 130°C / 10 minutes. In this manner, a diaphragm 7 for alkaline water electrolysis was obtained in which a coating layer was formed on the main surface of the porous support. Measurements of the overall thickness, the thickness of the coating layer, a particle shedding resistance test, and membrane resistance were performed on the alkaline water electrolysis diaphragm 7. The results are shown in Table 1.
[0129] <Example 8> (1. Formation of the main layer) The main layer was formed in the same manner as in Example 1.
[0130] (2. Formation of coating layer) The coating layer forming composition 2 was diluted to a 1% by mass aqueous solution, which was stored in a tray. A crosslinking agent (Carbodilite SV-02, manufactured by Nisshinbo Chemical Co., Ltd.) was added thereto. The content of the crosslinking agent was 10% by mass relative to the solid content of the coating layer forming composition 2. The surfaces of the porous membrane and the porous support, which were wet with water, were each brought into contact with the aqueous solution, and then dried under the conditions of 130°C / 10 minutes. In this manner, a diaphragm 8 for alkaline water electrolysis was obtained, in which a coating layer was formed on the main surface of the porous membrane and the main surface of the porous support. The diaphragm 8 for alkaline water electrolysis was subjected to measurement of the overall thickness, measurement of the thickness of the coating layer, a particle shedding resistance test, and measurement of the membrane resistance. The results are shown in Table 1.
[0131] <Comparative Example 1> A main layer was formed in the same manner as in Example 2 to prepare a comparative diaphragm C1 for alkaline water electrolysis. For the diaphragm C1 for alkaline water electrolysis, measurements of the overall thickness, the thickness of the coating layer, resistance to particle shedding, and membrane resistance were performed. The results are shown in Table 1.
[0132] [Table 1]
[0133] From Table 1, it was found that the diaphragms for alkaline water electrolysis of Examples having a coating layer formed thereon had a smaller weight loss rate after the dropping test and dropped-off of inorganic particles was suppressed, compared with the diaphragms for alkaline water electrolysis of Comparative Examples having no coating layer formed thereon. Furthermore, the diaphragms for alkaline water electrolysis having a coating layer formed thereon had a membrane resistance of 1.00 Ωcm 2 The film resistance was less than 100 μm, indicating good film resistance.
Claims
1. A porous support; a porous membrane provided on one or both main surfaces of the porous support, the porous membrane containing inorganic particles and an organic resin, Further, a coating layer containing a polymer having an acid group is provided on one or both sides in the thickness direction of the main layer composed of the porous support and the porous membrane. A diaphragm for alkaline water electrolysis characterized in that
2. The diaphragm for alkaline water electrolysis according to claim 1, wherein the polymer has a carboxy group.
3. The diaphragm for alkaline water electrolysis according to claim 1 or 2, wherein the coating layer comprises a coating layer-forming composition comprising the polymer and a crosslinking agent.
4. The diaphragm for alkaline water electrolysis according to claim 1 or 2, wherein the coating layer contains the inorganic particles only on the main layer side.
5. The diaphragm for alkaline water electrolysis according to claim 1 or 2, wherein the coating layer has a thickness of 0.05 to 5.00 µm.
6. The diaphragm for alkaline water electrolysis according to claim 1 or 2, wherein the porous membrane is provided on only one main surface of the porous support.
7. The diaphragm for alkaline water electrolysis according to claim 1 or 2, wherein the porous membrane is provided on both main surfaces of the porous support.
8. The diaphragm for alkaline water electrolysis according to claim 1 or 2, wherein the inorganic particles contain at least one kind selected from the group consisting of magnesium hydroxide, zirconium oxide, titanium oxide, and barium sulfate.
9. The diaphragm for alkaline water electrolysis according to claim 1 or 2, wherein the organic resin contains at least one selected from the group consisting of polysulfone, polyethersulfone, and polyphenylsulfone.
10. The diaphragm for alkaline water electrolysis according to claim 1 or 2, wherein the porous support is a nonwoven fabric, a woven fabric, or a mesh comprising at least one material selected from the group consisting of polypropylene, polyethylene, and polyphenylene sulfide.
11. The membrane resistance is 0.10 to 1.00 Ωcm 2 The diaphragm for alkaline water electrolysis according to claim 1 or 2, which is
12. A method for producing the diaphragm for alkaline water electrolysis according to claim 1 or 2, comprising the steps of: A step of attaching a composition for forming a porous membrane, which comprises inorganic particles and an organic resin, to a porous support; contacting the porous support with a non-solvent to form a body layer; a step of applying a coating layer-forming composition containing a polymer having an acid group to the main body layer in a state wetted with the non-solvent, and then drying the composition to form a coating layer.
2. The method for producing a diaphragm for alkaline water electrolysis, comprising:
Citation Information
Patent Citations
Production method of diaphragm for alkali water electrolysis
JP2021090909A